Some Multidimensional Inverse Problems of Memory Determination in Hyperbolic Equations - Durdiev, D. K. (Журнал математичної фізики, аналізу, геометрії, 2007)
The local existence and the uniqueness of some multidimensional inverse problems for the second-order hyperbolic integro-differential equations in the class of functions having certain smoothness on time variable and analyticity on a part of spatial variables are proven. Mathematics Subject Classification: 35L10.